The removal of chromium (VI) and lead (II) from groundwater using sepiolite-supported nanoscale zero-valent iron (S-NZVI). (November 2015) - Fu, Rongbing; Yang, Yingpin; Xu, Zhen; Zhang, Xian; Guo, Xiaopin; Bi, Dongsu
Highlights: NZVI was immobilized on sepiolite to overcome agglomeration. Heavy metals were rapidly and extensively remediated by sepiolite-supported NZVI. The remediation of metals occurred in a stepwise manner (adsorption–reduction). Sepiolite-supported NZVI could be applied to in situ heavy metal remediation. Abstract: In this study, the synthesis and characterization of sepiolite-supported nanoscale zero-valent iron particles (S-NZVI) was investigated for the adsorption/reduction of Cr(VI) and Pb(II) ions. Nanoscale zero-valent iron (NZVI) supported on sepiolite was successfully used to remove Cr(VI) and Pb(II) from groundwater with high efficiency. The removal mechanism was proposed as a two-step interaction including both the physical adsorption of Cr(VI) and Pb(II) on the surface or inner layers of the sepiolite-supported NZVI particles and the subsequent reduction of Cr(VI) to Cr(III) and Pb(II) to Pb(0) by NZVI. The immobilization of the NZVI particles on the surface of sepiolite could help to overcome the disadvantage of NZVI particles, which have strong tendency to agglomerate into larger particles, resulting in an adverse effect on both the effective surface area and reaction performance. The techniques of XRD, XPS, BET, Zeta potential, and TEM were used to characterize the S-NZVI and interaction between S-NZVI and heavy metals. The appropriate S-NZVI dosage was 1.6 g L −1 . The removal efficiency of Cr(VI) and Pb(II) by S-NZVI was not affected to any considerable extent by the presence of co-existing ions, such as H2 PO4 −, SiO3 2−, Ca 2+ and HCO3 − . The Cr(VI) and Pb(II) removal kinetics followed a pseudo-first-order rate expression, and both Langmuir isotherm model and Freundlich isotherm model were proposed. The results suggested that supporting NZVI on sepiolite had the potential to become a promising technique for in situ heavy metal-contaminated groundwater remediation.